Особенности идиолекта главной героини мультфильма «Маша и медведь» и их передача в переводе на польский язык - Didenko, Natalya (Acta Polono-Ruthenica, 2019)
This paper deals with the properties of the idiolect used by the main character of Masha and the Bear animated film and the ways in which they are rendered into the Polish language. In the film, the properties of Masha’s idiolect have a characterising function. They are as follows: (1) the repetitiveness of syntactical structures (including exclamatory sentences); (2) linguistic creativeness (i.e. creating occasional vocabulary); (3) the use of colloquial lexis; (4) grammatical and lexical mistakes. The properties of Masha’s idiolect are not always rendered in translation. Therefore, in the target text, there is a character whose linguistic properties are different from the ones she has in the source text. However, the primary task of the translator is to create an equivalent which could be perceived by the target audience as belonging to their native language, devoid of artificiality (especially for children). It is thus frequently related to the necessity to introduce some modifications of the idiolectal properties of the main characters.